MENINGKATKAN MOTIVASI SISWA BELAJAR MUSIK RECORDER MELALUI METODE PERMODELAN - Neti Lestari; Ardipal Ardipal; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2013)
Abstract This research was aimed at revealing the use of modeling method to improve the student’ skill in playing recorder.The subject of the research was the students in class VIII6of SMP Negeri 2 Kota Pariaman registered in academic year 2012-2013. This was a classroom action research.The result of the research indicated that there was an improvement on the student’ learning achievement after the method applied. In pre-cycle, the average score of the students was 68,14286 and it improved into 73,85714 in the first cycle. In the second cycle it became 82. Thus, it can be concluded that the modeling method could be used to help the students in learning. Keyword: teacher, student, recorder music,modeling method.